Calcium Pre-Rinse: Effect on permeability of dentin tubules by fluoride rinse - Braga, Tacíria-Machado-Bezerra (J Clin Exp Dent, 2019)
BACKGROUND: The aim of this study was to evaluate whether calcium (CaL) solution would enhance the capacity of sodium fluoride (NaF) solution in reducing the permeability of hypersensitive dentin. MATERIAL AND METHODS: Thirty-two Wistar rats ingested for 45 days acidic isotonic drink (Gatorade, pH 2.7) ad libitum to induce dental erosion. Then, molar teeth received a cold stimulus to confirm the presence and score the intensity of dentin hypersensitivity based on body contraction and noise. Animals were allocated to four groups (n=8), according to the solution(s) applied in the oral cavity: NaF (12 mmol/L, 1 min); CaL (150 mmol/L, 1 min); CaL followed by NaF (CaF+NaF, 1 min each); distilled water (DW, 1 min, as negative control). The animals were euthanized and the mandibles dissected into hemimandibles, which were sealed with sticky wax, except for the occlusal surface of the molar teeth. The samples were immersed in 10% copper sulphate solution and in 1% dithioxamide alcoholic solution (25 min each). The samples were sectioned longitudinally and imaged under optical microscope. Then, dentin permeability was measured as the area of copper ion penetration, using ImageJ software. Photomicrographs were obtained by scanning electron microscopy. RESULTS: 68.7% of animals had body contraction associated or not with noise. One-way ANOVA followed by Tukey´s test indicated that groups treated with NaF solution, whether or not preceded by CaL solution, presented lower permeability than the remaining groups [CaL+NaF: 3405.7 μm2 (±1796.4); NaF: 4111.7 μm2 (±2450.6); CaL: 42254.6 μm2 (±30399.2); DW: 37064.6 μm2 (±21994.4)]. Photomicrographs showed that CaL+NaF group presented an increased proportion of occluded dentin tubules in comparison to the NaF-only group. CONCLUSIONS: Although qualitatively there seems to be a benefit in using CaL pre-rinse, this solution did not quantitatively enhance the capacity of NaF in reducing permeability of hypersensitive dentin. Key words:Dentin hypersensitivity, Fluoride, Calcium lactate, Animal model.